$\mathbb{S}\text{ol}^{3}× \mathbb{E}^{1}$-MANIFOLDS. (4th December 2017) - HILLMAN, J. A.
Abstract : We show that closed $\mathbb{S}\text{ol}^{3}× \mathbb{E}^{1}$ -manifolds are Seifert fibred, with general fibre the torus, and base one of the flat 2-orbifolds $T, Kb, \mathbb{A}, \mathbb{M}b, S(2, 2, 2, 2), P(2, 2)$ or $\mathbb{D}(2, 2)$, and outline how such manifolds may be classified.